Development of The "Daring to Face Shocks" Book to Improve Earthquake Disaster Mitigation Skills in Early Childhood At Bekasi Nature School - Alvya Noer Hikmarani; Muhammad Zid; Cahyadi Setiawan (Al Qalam: Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2025)
This study aims to improve earthquake disaster mitigation skills in early childhood by using a picture storybook that incorporates storytelling and role-playing methods. The research was conducted at Sekolah Alam Bekasi from February to April 2025. A mixed-method approach was employed, integrating both quantitative and qualitative techniques. The population consisted of all kindergarten students at Sekolah Alam Bekasi, totaling 60 children. A sample of 30 students was selected through purposive random sampling. Data were collected using interviews and questionnaires. The book Berani Menghadapi Guncangan was rated highly feasible with a feasibility score of 93.75%. Student responses indicated a very high level of interest, reaching 98.7%. Their knowledge of earthquake mitigation increased significantly, as shown by an N-Gain score of 0.7742, which exceeds the 0.7 threshold and is therefore considered effective, with an overall effectiveness level of 77%. Therefore, it can be concluded that book Berani Menghadapi Guncangan is not only interesting, but also has a significant impact on disaster mitigation learning. This makes the book highly suitable and effective for disaster education for early childhood.